2022
DOI: 10.1038/s41386-022-01301-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeated lysergic acid diethylamide (LSD) reverses stress-induced anxiety-like behavior, cortical synaptogenesis deficits and serotonergic neurotransmission decline

Abstract: Lysergic acid diethylamide (LSD) is a serotonergic psychedelic compound receiving increasing interest due to putative anxiolytic and antidepressant properties. However, the potential neurobiological mechanisms mediating these effects remain elusive. Employing in vivo electrophysiology, microionthophoresis, behavioral paradigms and morphology assays, we assessed the impact of acute and chronic LSD administration on anxiety-like behavior, on the cortical dendritic spines and on the activity of serotonin (5-HT) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 68 publications
4
31
0
Order By: Relevance
“…Lasting adaptations in synaptic homeostasis have been linked to the therapeutic potential of psychedelics, which ultimately suggests that different postacute effects could share a common mechanistic substrate and impact one another. Since recent observations indicate that repeated LSD reverses stress-induced anxiety-like behavior and cortical synaptic plasticity deficits in mice, it will be interesting to expand this concept in future studies to characterize the function of these genes in processes related to synaptic plasticity, as well as the role of psychedelic-induced down-regulation of frontal cortex 5-HT 2A R density in these long-lasting therapeutic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Lasting adaptations in synaptic homeostasis have been linked to the therapeutic potential of psychedelics, which ultimately suggests that different postacute effects could share a common mechanistic substrate and impact one another. Since recent observations indicate that repeated LSD reverses stress-induced anxiety-like behavior and cortical synaptic plasticity deficits in mice, it will be interesting to expand this concept in future studies to characterize the function of these genes in processes related to synaptic plasticity, as well as the role of psychedelic-induced down-regulation of frontal cortex 5-HT 2A R density in these long-lasting therapeutic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, DMT has been seen to enhance both neurogenesis and memory performance [44]. Other studies have reported improvements in fear extinction learning and reductions in anxious behaviors and learned helplessness following exposure to psychedelics, while also observing increased dendritic spine density in separate cohorts of animals [27,37,103]. Finally, the enhanced spinogenesis induced by ketamine, which is also a psychoplastogen, has been associated with reductions in depression-related behaviors [117,118].…”
Section: Consequences Of Enhanced Neuroplasticitymentioning
confidence: 97%
“…Psychedelics have been shown to enhance dendritic growth, including spinogenesis, in cortical neurons [36,40]. In the frontal lobe specifically, animal studies show that psychedelics upregulate plasticity-related genes and promote the growth of synapses and dendritic spines [25,27,36,37,103]. In the prefrontal cortex (PFC), several psychedelics have been shown to rapidly upregulate genes related to neuroplasticity [25,26,104].…”
Section: Neocortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the effects of serotoninergic psychedelics on stress coping in rodents [ 12 , 89 , 103 , 104 , 105 , 106 , 107 ]. One previous study found that a single administration of DOI did not have an acute effect on immobility behavior in the forced swim test in rats [ 42 ].…”
Section: Discussionmentioning
confidence: 99%